Audit of a Competitive Intelligence Unit. Issue 3 (2nd September 2017) - Izquierdo Triana, Héctor; Fernández, José Luis; Ballesté, Eva
ABSTRACT: The Spanish business environment associates the function of competitive intelligence (CI) to customer-focused marketing area. The fact that competitive intelligence is not seen as a high value-added tool in terms of security, technological vigilance, and strategic vision makes us ask ourselves if Spanish companies realize that CI is an essential source for improving competitiveness and verify if companies have implemented this function appropriately. This article proposes a review of the CI implementation process in Spanish companies. This research work provides an audit of processes carried out with the objective of identifying areas of improvement not only in the implementation but also in the sustainability of the intelligence programs so the reader can audit a function in terms of sustainability of the program. According to this research, the scope of the auditory work in CI is in initial phases, more centered on the auditing of resources than intelligence, the focus of the audits in CI is based on the measures of product control and usability for clients and the implementation of CI audits in Spanish companies as a way of strengthening and legitimizing CI units. Finally, based on the results and needs of the study, we propose a CI auditing process.